Can Vascular Endothelial Growth Factor and Microvessel Density Be Used as Prognostic Biomarkers for Colorectal Cancer? A Systematic Review and Meta-Analysis - Yibaina Wang; Xiaoping Yao; Jie Ge; Fulan Hu; Yashuang Zhao (The Scientific World Journal)
Background. Vascular endothelial growth factor (VEGF) and microvessel density (MVD) are associated with greater incidence of metastases and decreased survival. Whether they can be used as prognostic indicators of colorectal cancer (CRC) is still controversial. Methods. The authors performed a meta-analysis using the results of a literature search of databases of PubMed and EMBASE, and the references of articles included in the analysis. Meta-analysis was performed using random effects model and hazard ratios (HRs) and 95% confidence intervals (CIs) as effect measures. Results. Twenty studies contributed to the analysis of VEGF, of which 16 were used for overall survival (OS) and 9 for disease-free survival (DFS). High VEGF levels has a relationship with unfavorable survival (OS: HR = 1.98, 95% CI: 1.30–3.02; DFS: HR = 2.10, 95% CI: 1.26–3.49) and a 4.22-fold increase in the rate of distant metastases. Analysis was performed on 18 studies for MVD; the results showed that patients with high MVD expression in tumors appeared to have poorer overall survival (HR = 1.39, 95% CI: 1.22–1.58) and were at a greater risk of having unfavorable clinical characteristics related to prognosis. Corresponding results were obtained from quantitative and/or qualitative analysis of clinicopathological. Conclusions. The meta-analysis demonstrates that VEGF and MVD can be used as prognostic biomarkers for CRC patients.